THE BONESETTER’S DAUGHTER: A STUDY IN THE EXPOSURE OF CHINESE CULTURE - ROSITA, LIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Rosita, Lia. 2013.  The Bonesetter’s Daughter: A Study in the Exposure of Chinese Culture.  Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya.Supervisor: Dyah Eko Hapsari; Co-supervisors: Fredy NugrohoKeywords: Chinese culture, Chinese traditions, superstitions belief.Amy Tan is one of famous Chinese – American novelist who produces so many literary works.  The Bonesetter’s Daughter  is one of Tan’s novels that published in 2001. The writer chooses Tan’s novel as her material object because the novel has interesting topic to analyze that is about the life of Chinese immigrants. In addition the writer uses Chinese studies especially about Chinese culture and tradition as her guidance to analyze the novel. The result of this study shows that there are so many exposures of Chinese culture which are portrayed in Tan’s  The Bonesetter’s Daughter. The writer finds about how Chinese  – American people enliven their original culture in the aspect Chinese tradition in their life in America, for example is about celebrating Chinese traditions as Chinese immigrant in America. The novel also presents the exposure of Chinese belief, like how the characters in novel believe in the existence of ghost and the power of dragon bone. From the result the writer concludes that Chinese people is a kind of strict people especially in keeping their original tradition wherever they stay and the novel shows how Tan exposes the idea about the importance of rerouting Chinese culture for Chinese – American.